2017
DOI: 10.1371/journal.pone.0177003
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator activity in tears of pregnant women

Abstract: PurposePlasminogen activator activity (PAA) in tears of pregnant women was investigated at various gestation times to assess the availability of plasminogen activator for aiding potential corneal wound healing processes during pregnancy.MethodsPAA was measured by a spectrophotometric method. The analysis used 91 tear samples from pregnant and non-pregnant women, supplemented with 10 additional tear PAA measurements from non-pregnant women obtained in a previous study.ResultsTear levels of PAA in pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…It should be of note that these cytokines which are the interleukin 6 and Tissue Necrotic Factor [TNF] are responsible for inducing the production of platelet and tissue plasminogen activator [tPA] in cases of coexistence of malaria with another condition that could lead to bleeding PAI-1 and PAI-2 were elevated in all the pregnant women though more elevated in malaria infected pregnant women than the other experimental groups. The observed elevation in all the pregnant women is in consonance with previous reports by [26] that plasminogen activators are elevated for the good of pregnant women and in gestational tissues as they are required for normal placentation especially the PAI-2. This result also agrees with the report of [27] which reported that increase in the concentration of PAI-1 and PAIinfected women could also be as result of large numbers of proinflammatory cytokines being released due to malaria infection as well as in pregnancy more over PAI-2 also increases as the pregnancy increases [27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It should be of note that these cytokines which are the interleukin 6 and Tissue Necrotic Factor [TNF] are responsible for inducing the production of platelet and tissue plasminogen activator [tPA] in cases of coexistence of malaria with another condition that could lead to bleeding PAI-1 and PAI-2 were elevated in all the pregnant women though more elevated in malaria infected pregnant women than the other experimental groups. The observed elevation in all the pregnant women is in consonance with previous reports by [26] that plasminogen activators are elevated for the good of pregnant women and in gestational tissues as they are required for normal placentation especially the PAI-2. This result also agrees with the report of [27] which reported that increase in the concentration of PAI-1 and PAIinfected women could also be as result of large numbers of proinflammatory cytokines being released due to malaria infection as well as in pregnancy more over PAI-2 also increases as the pregnancy increases [27].…”
Section: Discussionsupporting
confidence: 91%
“…This finding agrees with the report by [3] and [12] 2 were elevated in all the pregnant women though more elevated in malaria infected pregnant women than the other experimental groups. The observed elevation in all the pregnant women is in consonance with [26] that plasminogen activators are elevated for the good of pregnant women and in gestational tissues as they are required for normal placentation especially the 2. This result also agrees with the report of [27] which reported that increase in the -2 in malaria infected women could also be as result of large numbers of proinflammatory cytokines being released due to malaria infection as well as in 2 also increases as Malaria and pregnancy in this study influenced dimer both in malaria positive pregnant and in malaria negative pregnant women respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Entrapped enzyme activity was assayed using a colourimetric method based on S‐2251 substrates [46, 47]. Substrate solution was prepared briefly by adding 1 ml Tris (0.5 M, pH = 7.4) and 5 μl Tween‐20 to 1 ml of 3 mM S‐2251.…”
Section: Methodsmentioning
confidence: 99%
“…6 If the stimulus to fibrinolysis is strong enough, tissue plasminogen activator levels stay normal during pregnancy, allowing the pregnant woman to create enough plasmin to eliminate unwanted fibrin clots from the bloodstream. 7 Because delivery is typically followed by an immediate increase in plasma fibrinolytic activity, it is suggested that the placenta is responsible for the decreased fibrinolytic activity that characterizes normal pregnancy. 8 Additionally, after delivery, fibrin degradation products typically increase significantly.…”
Section: Introductionmentioning
confidence: 99%